UPAYA PENINGKATAN KUALITAS PENDIDIKAN ANAK MELALUI PROGRAM KERJA RUMAH BELAJAR DI DESA SIGAMBO-GAMBO TAPANULI TENGAH - Ahmad Burhanuddin; Sawaluddin Siregar; Ratna Ayu Pawestri Kusuma Dewi; Muhammad Iskandar Dzulkurnain (Yayasan Baitul Hikmah al-Zain, 2024)
Education in Sigambo-gambo Village is an education that is classified as minimal in terms of human resources, namely teaching staff and facilities that can support the teaching and learning process of children. So as to create the quality of the young generation below average. In this article, the author uses the Participatory Action Reasearch approach. The work program formed is in the form of a Learning House work program which is specifically for children in Sigambo-gambo Village in an effort to improve the quality of education. With the realization of the Learning House work program for elementary to junior high school children in Sigambo-gambo Village. Able to provide excellent development for children